Використання сучасних технологій та інструментів для організації live ефірів - Горошко, А. І. (ХНУРЕ, 2023)
Live streaming is becoming increasingly popular in the media industry. This allows content to be delivered to viewers around the world in real time. In order for these broadcasts to be successful, it is necessary to use modern technologies and tools for their organization. One of the most popular tools is OBS Studio, which can be used to stream content from multiple sources simultaneously. It also has a wide range of features such as audio mixing, video mixing and more.
Keywords: ефір